2003
DOI: 10.1007/bf03040335
|View full text |Cite
|
Sign up to set email alerts
|

Appointments at a thyroid outpatient clinic and the lunar cycle

Abstract: Our findings suggest that lunar phases may affect patients' requests for appointments at a thyroid outpatient clinic. To the best of our knowledge, this is the first study reporting a possible association between health-related behaviour and lunar phases using requests for appointments as a relevant variable. There is a need for more research into the mechanism underpinning this behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Similarly, it has been surmised that the moon may have an impact on the psychological basis of normal and abnormal behaviour resulting in e.g. uicide, parasuicide, fluctuation in consulting rates with general practitioners and in emergency departments [16][17][18][19][20][21][22]. Most of these studies failed to detect any impact of the moon on the parameter investigated.…”
Section: Introductionmentioning
confidence: 98%
“…Similarly, it has been surmised that the moon may have an impact on the psychological basis of normal and abnormal behaviour resulting in e.g. uicide, parasuicide, fluctuation in consulting rates with general practitioners and in emergency departments [16][17][18][19][20][21][22]. Most of these studies failed to detect any impact of the moon on the parameter investigated.…”
Section: Introductionmentioning
confidence: 98%
“…Several papers reported associations between the lunar cycle and the frequency of hospital admissions due to various causes: cardiovascular disease [13], acute coronary events [14], gastrointestinal hemorrhage [15] and infectious diarrhea [16]. Lunar phases were also associated with the number of requests for appointment at a thyroid outpatient clinic [17]. On the other hand, a number of studies showed insufficient evidence or no association between various health-related events and the synodic lunar cycle [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Associations between lunar cycles and health conditions, however, such as increased phone call rates by females to a crisis-call centre, higher frequency in misbehaviors in institutionalized patients, greater behavioral deterioration in patients with schizophrenia, increased occurrence in gout attacks, and higher frequencies in the number of appointment requests in thyroid outpatients; rates of gastrointestinal bleeding; multiparae delivery rates; and numbers of births, have been reported [16-23]. …”
Section: Introductionmentioning
confidence: 99%